Reliability and Perceived Ease of Use Mediate Customer E-Trust Towards Customer E-Retention - Fitriani, Nur Afika; Siswanto, Ely; Wilujeng, Ita Prihatining (Jurnal Ilmu Manajemen Profitability, 2025)
This study investigates the mediating role of reliability and perceived ease of use in shaping customer e-trust and its subsequent influence on customer e-retention within the TikTok Shop platform. Grounded in the Technology Acceptance Model (TAM), the research employs a quantitative explanatory approach with a purposive sampling method, involving 80 respondents from TikTok Shop consumers in Malang City. Data were collected using structured online questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0. The findings reveal that both reliability and perceived ease of use exert a positive and significant effect on customer e-trust, underscoring the importance of consistent system performance and user-friendly features in strengthening customer confidence. Moreover, reliability demonstrates a direct and significant influence on customer e-retention, indicating that customers who perceive the platform as dependable are more likely to remain loyal. In contrast, perceived ease of use does not directly affect customer e-retention, suggesting that while ease of navigation and interaction enhance trust, they are insufficient on their own to secure long-term retention. Importantly, customer e-trust significantly mediates the relationship between both reliability and perceived ease of use toward customer e-retention, highlighting trust as a critical mechanism for sustaining loyalty. These findings contribute to the literature on digital consumer behavior and provide practical implications for e-commerce platforms to prioritize trust-building strategies through system reliability and ease of use.